Overexpression of E2F1 in human gastric carcinoma is involved in anti-cancer drug resistance - Yan, Lin-Hai (BMC Cancer, 2014)
BACKGROUND: Routine chemotherapy often cannot achieve good therapeutic effects because of multidrug resistance (MDR). MDR is frequently caused by the elevated expression of the MDR1 gene encoding P-glycoprotein (P-gp). E2F1 is a frequently overexpressed protein in human tumor cells that increases the activity of the MDR1 promoter, resulting in higher P-gp levels. The upregulation of P-gp might contribute to the survival of tumor cells during chemotherapy. E2F1 confers anticancer drug resistance; however, we speculate whether E2F1 affects MDR through other pathways. This study investigated the possible involvement of E2F1 in anticancer drug resistance of gastric carcinoma in vitro and in vivo. METHODS: A cisplatin-resistant SGC7901/DDP gastric cancer cell line with stable overexpression of E2F1 was established. Protein expression levels of E2F1, MDR1, MRP, TAp73, GAX, ZEB1, and ZEB2 were detected by western blotting. The influence of overexpression of E2F1 on anticancer drug resistance was assessed by measuring IC50 of SGC7901/DDP cells to cisplatin, doxorubicin, and 5-fluorouracil, as well as the rate of doxorubicin efflux, apoptosis, and cell cycle progression detected by flow cytometry. We determined the in vivo effects of E2F1-overexpression on tumor size in nude mice, and apoptotic cells in tumor tissues were detected by deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling and hematoxylin and eosin staining. RESULTS: The SGC7901/DDP gastric cancer cell line stably overexpressing E2F1 exhibited significantly inhibited sensitivity to cisplatin, doxorubicin, and 5-fluorouracil. Flow cytometry confirmed that the percentage of apoptotic cells decreased after E2F1 upregulation, and that upregulation of E2F1 potentiated S phase arrest of the cell cycle. Furthermore, upregulation of E2F1 significantly decreased intracellular accumulation of doxorubicin. Western blot revealed that E2F1 upregulation suppressed expression of GAX, and increased the expression of MDR1, MRP, ZEB1, TAp73, and ZEB2. CONCLUSIONS: Overexpression of E2F1 promotes the development of MDR in gastric carcinoma, suggesting that E2F1 may represent an efficacious target for gastric cancer therapy.